2019
DOI: 10.4085/1403208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Procedure Type on Core Competency Implementation by Athletic Training Students

Abstract: Context: Core competencies (CCs) are now a required component of educational content in all types of Commission on Accreditation of Athletic Training Education-accredited athletic training programs. There is limited evidence demonstrating which procedures included during patient encounters (PEs) occurring in clinical education allow for implementation of CCs.Objective: To determine the relationship between procedures performed by athletic training students during PEs on CC implementation. Design: Panel design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The opportunities at the clinical site also affect core competency use. 10 Particularly for PCC, athletic training students who performed orthopaedic evaluation, manual therapy, and therapeutic rehabilitation were 3.6, 2.6, and 1.9 times, respectively, more likely to implement PCC. 10 Program directors who want their athletic training students to gain clinical experience in performing PCC should encourage clinical preceptors to provide athletic training students these specific opportunities to incorporate not only clinical skills but PCC skills at their clinical sites.…”
Section: Patient-centered Carementioning
confidence: 99%
See 2 more Smart Citations
“…The opportunities at the clinical site also affect core competency use. 10 Particularly for PCC, athletic training students who performed orthopaedic evaluation, manual therapy, and therapeutic rehabilitation were 3.6, 2.6, and 1.9 times, respectively, more likely to implement PCC. 10 Program directors who want their athletic training students to gain clinical experience in performing PCC should encourage clinical preceptors to provide athletic training students these specific opportunities to incorporate not only clinical skills but PCC skills at their clinical sites.…”
Section: Patient-centered Carementioning
confidence: 99%
“…10 Program directors who want their athletic training students to gain clinical experience in performing PCC should encourage clinical preceptors to provide athletic training students these specific opportunities to incorporate not only clinical skills but PCC skills at their clinical sites. 10 Lastly, to mitigate the incongruence identified in our results, we suggest that instructional techniques such as direct observation, standardized patient exams with live actors, bug-in-ear technology, and video modeling of previous patient interactions be used to promote self-reflection and future practice habit changes that integrate PCC principles. [56][57][58] Gender Minority Care…”
Section: Patient-centered Carementioning
confidence: 99%
See 1 more Smart Citation
“…As athletic training continues to emphasize the CCs, it is important to ensure that ATSs are exposed to PE opportunities that promote the inclusion of professional behaviors related to the CCs. Previous researchers 8 have focused on ATSs reporting whether they thought they had implemented CCs during a PE but did not provide details of which aspects (ie, professional behaviors) of the CCs were being implemented. In addition, the investigators 8,10 who conducted studies in this area collected PE data from only 1 professional athletic training program during a single academic semester.…”
Section: Discussionmentioning
confidence: 99%
“…5 The CCs identified for athletic training have been well defined in the literature. [6][7][8] However, whereas previous researchers 7,9 found that these CCs could be demonstrated through a variety of professional behaviors, continued emphasis has been placed on the intertwining of the CCs and the importance of not implementing them individually. 7 For example, determining the best concussion treatment protocol for a patient requires an understanding of current best practices (EBP), coordination with other health care professionals (IPECP), and consideration of patient history (HIT), goals (PCC), and activities of daily living (PCC) and might require clinicians to evaluate emerging evidence on treatment and assessment techniques (EBP).…”
mentioning
confidence: 99%